THE EFFICIENCY OF LOCAL ENDOSCOPIC INJECTION THERAPY IN ACUTE UPPER GASTROINTESTINAL HEMORRHAGE DUE TO PEPTIC ULCERS - Nadir YÖNETİCİ and Ahmet AYDIN and Ömer ÖZÜTEMİZ and Ahmet MUSOĞLU and Yücel BATUR and Hanefi ÇAVUŞOĞLU (Turkish Journal of Gastroenterology, 2020)
-